Предмет: Алгебра,
автор: nastenka2012
(x-2)^4-5(x^2-4)^2+4(x+2)^4=0
Ответы
Автор ответа:
0
(x-2)^4-5(x^2-4)^2+4(x+2)^4 = 24x^3+160x^2 + 96x = 8x(3x^2+20x+12)=0
x=0
3x^2+20x+12=0
D=400-4*3*12 =V256=16
x=-20+16/ 6=-4/6=-2/3
x=-20-16 / 6=-6
Ответ 0 -2/3 -6
Автор ответа:
0
(x-2)^4-5(x^2-4)^2+4(x+2)^4=0
x^4-8x^3+24x^2-32x+16-5x^4+40x^2-80+4*(x+2)^4=0
-4x^4-8x^3+64x^2-32x-64+4x^4+32x^3+96x^2+128x+64=0
-8x^3+64x^2-32x-64+32x^3+96x^2+128x+64=0
24x^3+160x^2-32x-64+128x+64=0
24x^3+160x^2+96x=0
Разложим на множители 24x^3+160x^2+96x:
8x*(x+6)*(3x+2)=0
8x=0
x1=0
x+6
x2=-6
3x+2=0
x3=-2/3
Похожие вопросы
Предмет: Математика,
автор: sajguzinasvetlana
Предмет: История,
автор: 28kodatcka28
Предмет: Қазақ тiлi,
автор: bajsugirkuandyk
Предмет: Математика,
автор: Аноним